Nitric oxide-releasing aspirin: will it say NO to atherothrombosis? - Antoniades, C; Tousoulis, D; Stefanadis, C (2007)
Aspirin is a powerful anti-platelet drug widely used in patients with coronary atherosclerosis, but its side effects and especially its toxicity for gastrointestinal tract limit its usefulness in specific groups of patients. A new category of agents, nitric oxide-releasing aspirins (such as NCX-4016), seems to provide an alternative solution. Although this drug is still at phase II clinical trials, it has provided promising results until now. When administered in vivo, it is separated into an aspirin moiety and an NO-donating complex, providing both the antithrombotic effect of aspirin and the gastroprotective effect of NO. Additionally, it increases NO bioavailability as a vascular level, and it may have the antiatherogenic properties of endogenously produced NO. Finally, recent evidence suggests that it may also improve functional aspects of vein grafts used in CABG, with possible benefit on graft patency. However, the outcome of the large ongoing trials is needed before any conclusion is made about the role of NO-releasing aspirins in cardiovascular disease.